Measuring the Success of Accounting Information Systems Using the DeLone and McLean Model: A Case Study of Cooperatives in Badung Regency - Ni Kadek Parissa Prawisanthi; Anak Agung Ngurah Agung Kresnandra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study empirically investigates the impact of information quality, system quality, and service quality on net benefits in cooperatives located in Badung Regency, specifically in Mengwi District. A quantitative research approach was employed, with non-probability sampling and purposive sampling as the chosen techniques. A total of 150 respondents, including cooperative managers and staff, participated in this study. Data analysis was performed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) through SmartPLS 4.0 software. The study found that information quality significantly influences net benefits through system use and user satisfaction. High-quality information is critical for effective system use and leads to greater user satisfaction, which ultimately contributes to higher net benefits for the cooperatives. Similarly, system quality was also found to significantly affect net benefits, with the use of high-quality systems increasing system use and improving user satisfaction, further enhancing the net benefits received by the cooperatives. However, service quality did not show a significant direct impact on net benefits, nor did it have any significant effect through the mediating variables of system use and user satisfaction. This finding suggests that while service quality is important in many contexts, in the case of cooperatives in this study, the quality of the information and the system itself play a more prominent role in determining the net benefits. The results of this study emphasize the importance of focusing on improving information and system quality to maximize the net benefits in cooperatives. Cooperatives should prioritize investments in information technology systems and ensure that the information provided is accurate and relevant to enhance system use and user satisfaction. This, in turn, will lead to greater overall benefits for the cooperatives in Mengwi District, Badung Regency.